Histoplasma capsulatum urinary antigen detection in a kidney transplant recipient with acute paracoccidioidomycosis: Case study and literature review - Oliveira Bastos, Matheus; Varon, Andréa Gina; Theodoro, Pedro Henrique Nascimento; Falcão, Eduardo Mastrangelo Marinho; Zancopé-Oliveira, Rosely Maria; do Valle, Antonio Carlos Francesconi; Almeida-Paes, Rodrigo; de Macedo, Priscila Marques (PLoS neglected tropical diseases, 2024)
Paracoccidioidomycosis (PCM) and histoplasmosis are endemic fungal diseases in South America. Both can lead to lung involvement with fungal dissemination progressing to systemic and severe clinical manifestations, especially in immunosuppressed hosts. As the population of immunosuppressed individuals has been rising, a higher occurrence of fungal infections is predicted in this setting. This poses challenges regarding the differential diagnosis due to overlapping clinical and laboratorial findings, hampering the management of cases. In this study, the authors discuss the occurrence of a false-positive Histoplasma urinary antigen detection in a kidney transplant recipient with acute PCM. Given the scarce information about this subject, a review on literature data is provided. A comprehensive literature search was conducted to investigate previous studies that found cross-reactivity between Histoplasma urinary antigen assays in human patients with confirmed diagnosis of PCM. Additionally, an update of PCM in transplant recipients is provided. The included studies reported 120 samples from patients with PCM tested for Histoplasma antigen, presenting an overall cross-reactivity of 51.67% and 17 cases of PCM in transplant recipients. CONCLUSIONS: The galactomannan urinary antigen developed to diagnose histoplasmosis can cross react with PCM, which may represent a concern in countries where both mycoses overlap.